2002
DOI: 10.1002/cncr.11002
|View full text |Cite
|
Sign up to set email alerts
|

Serum insulin‐like growth factor I evaluation as a useful tool for predicting the risk of developing hepatocellular carcinoma in patients with hepatitis C virus‐related cirrhosis

Abstract: BACKGROUNDAlthough experimental studies have demonstrated an important role of insulin‐like growth factor I (IGF‐I) in hepatocarcinogenesis, the clinical data about IGF‐I in patients with hepatocellular carcinoma (HCC) are scarce and controversial. To the authors' knowledge, this is the first prospective study investigating the longitudinal correlation between modifications in serum IGF‐I levels and the development of HCC in a cohort of patients with hepatitis C virus (HCV)‐related cirrhosis.METHODSOne hundred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
64
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 32 publications
13
64
1
Order By: Relevance
“…Also, our results are in agreement with the findings of Orsini et al [25] who found similar results in hepatosplenic schistosomiasis patients and the results of Mazziotti et al [26] in patients with hepatocellular carcinoma (HCC) and hepatitis C vir us-related cirrhosis. The reduction in IGF-1 level also can precede the diagnosis of HCC [26] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Also, our results are in agreement with the findings of Orsini et al [25] who found similar results in hepatosplenic schistosomiasis patients and the results of Mazziotti et al [26] in patients with hepatocellular carcinoma (HCC) and hepatitis C vir us-related cirrhosis. The reduction in IGF-1 level also can precede the diagnosis of HCC [26] .…”
Section: Discussionsupporting
confidence: 93%
“…Also, our results are in agreement with the findings of Orsini et al [25] who found similar results in hepatosplenic schistosomiasis patients and the results of Mazziotti et al [26] in patients with hepatocellular carcinoma (HCC) and hepatitis C vir us-related cirrhosis. The reduction in IGF-1 level also can precede the diagnosis of HCC [26] . Similarly, decreased serum IGF-1 level has been recorded both in patients with viral cirrhosis [9,27] and in patients with hepatitis B infection without cirrhosis [28] .…”
Section: Discussionsupporting
confidence: 93%
“…The serum levels of IGFⅠ are significantly lower in patients with HCC compared with patients without HCC [49] . At a threshold of 4.1 mg/g IGFⅠ has a 63% sensitivity and a 90% specificity for diagnosings of HCC.…”
Section: Igfmentioning
confidence: 85%
“…However, the relevance of IGF-I to hepatocellular carcinoma is somewhat different from other malignancies because the majority of circulating IGF-I is produced by the liver (25) .…”
Section: Evaluation Of Taline-1 Mcp-1 and Igf-1 In Prediction Of Devmentioning
confidence: 99%